Pembinaan Bahasa Indonesia di Ruang Digital: Studi Pemanfaatan Instagram untuk Pengenalan Padanan Kata - Khoiriyah, Alvi Maryamul; Salsa, Elva Elfiani; Lontoh, Rhea Renata; Ertinawati, Yuni (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2025)
This study aims to describe strategies for Indonesian language development through the use of Instagram, particularly the Story feature, as a medium for introducing Indonesian lexical equivalents. The study is grounded in the increasing use of foreign terms and code-mixing on social media, highlighting the need for language cultivation efforts that align with digital communication habits. A descriptive qualitative method was employed, with data collected from polls, question box responses, and user interaction metrics from the Instagram account @katasetara_. The findings indicate that respondents’ understanding of Indonesian lexical equivalents remains relatively low, as shown by the high percentage of incorrect answers for terms such as caption (57%), typo (56%), and headset (52%). By providing explanations in feed posts, the @katasetara_ account serves as an informative and engaging medium for language cultivation. This study concludes that Instagram holds strong potential as an effective platform for linguistic education when combined with interactive strategies and adherence to standard Indonesian language norms.